2022
DOI: 10.3389/fendo.2022.948338
|View full text |Cite
|
Sign up to set email alerts
|

Low-normal serum unconjugated bilirubin levels are associated with late but not early carotid atherosclerotic lesions in T2DM subjects

Abstract: AimsWe aimed to examine the association of serum unconjugated bilirubin (UCB) within normal limits with carotid atherosclerosis in Chinese patients with type 2 diabetes mellitus (T2DM).MethodsThis cross-sectional, real-world study was performed in 8,006 hospitalized T2DM patients including 4,153 men and 3,853 women with normal UCB. The subjects were stratified into quintiles based on serum UCB levels (<6.2, 6.2–7.9, 8.0–8.9, 9.0–10.9, and >10.9 μmol/l, respectively). Carotid atherosclerotic lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…For example, in some chronic and acute in ammatory diseases such as metabolic syndrome, atherosclerosis, non-alcoholic fatty liver disease, and ulcerative colitis, elevated UCB showed a negative association with the occurrence and progression of these diseases (5,14,44,45). Our recent study also showed that high-normal UCB was closely associated with the decreased risk of carotid plaque and stenosis through its anti-in ammation effect in T2DM subjects (43). Therefore, the protective roles of UCB in DR may be partially attributed to its anti-in ammatory effect.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…For example, in some chronic and acute in ammatory diseases such as metabolic syndrome, atherosclerosis, non-alcoholic fatty liver disease, and ulcerative colitis, elevated UCB showed a negative association with the occurrence and progression of these diseases (5,14,44,45). Our recent study also showed that high-normal UCB was closely associated with the decreased risk of carotid plaque and stenosis through its anti-in ammation effect in T2DM subjects (43). Therefore, the protective roles of UCB in DR may be partially attributed to its anti-in ammatory effect.…”
Section: Discussionmentioning
confidence: 63%
“…In addition to its role as a reducing agent, UCB also inhibits in ammatory responses resulting from innate and acquired immunity (42). Meanwhile, the anti-in ammatory effect of mildly elevated UCB has been con rmed by many studies including our recent clinical study (43). For example, in some chronic and acute in ammatory diseases such as metabolic syndrome, atherosclerosis, non-alcoholic fatty liver disease, and ulcerative colitis, elevated UCB showed a negative association with the occurrence and progression of these diseases (5,14,44,45).…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, our study provides novel evidence that bilirubin could potentially serve as a prognostic biomarker specifically in the high-risk diabetic population. [50][51][52][53] However, there are limitations including the small sample size from a single center. Further research with expanded populations are warranted to validate the prognostic utility of bilirubin.…”
Section: Discussionmentioning
confidence: 99%
“…The normal value range of UCB was not available because it was not directly examined. According to the diagnostic criteria of our hospital‐automated analyser mentioned above and our recent study, 46 the normal range of STB is 0–18 μmol/L and CB 0–6 μmol/L. We excluded the patients with STB >18 μmol/L or/and CB >6 μmol/L in the present study.…”
Section: Methodsmentioning
confidence: 99%